Restricción a la asociacion sindical y la negociacion colectiva por la flexibilizacion laboral propuesta por la ley 50 (2016)
Labor reforms in Colombia have hurt job stability , the creation of intermediaries in labor relations considerably impairs the participation of workers in unions. The workers union Bancolombia has been damaged in this context , so it is necessary to analyze the regressive points that harm the collective right inspired from Act No. 50 of 1990. In order to glimpse the need to protect the right to limit trade union without the will of any worker to claim their employers better working conditions